Electrografting of Diazonium‐Functionalized Polyoxometalates: Synthesis, Immobilisation and Electron‐Transfer Characterisation from Glassy Carbon. Issue 41 (3rd September 2013) - Rinfray, Corentin; Izzet, Guillaume; Pinson, Jean; Gam Derouich , Sarra; Ganem, Jean‐Jacques; Combellas, Catherine; Kanoufi, Frédéric; Proust, Anna
Abstract Polyoxometalates (POMs) are attractive candidates for the rational design of multi‐level charge‐storage materials because they display reversible multi‐step reduction processes in a narrow range of potentials. The functionalization of POMs allows for their integration in hybrid complementary metal oxide semiconductor (CMOS)/molecular devices, provided that fine control of their immobilisation on various substrates can be achieved. Owing to the wide applicability of the diazonium route to surface modification, a functionalized Keggin‐type POM [PW11O39Ge(p‐C6H4‐CC‐C6H4‐ <![CDATA[N+2]]> <inline-graphic xlink:href="ark:/27927/pgg3j1pnsrp" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />)]3− bearing a pending diazonium group was prepared and subsequently covalently anchored onto a glassy carbon electrode. Electron transfer with the immobilised POM was thoroughly investigated and compared to that of the free POM in solution.